COVID-19 caseness: An epidemiologic perspective - Abdel-Hady El-Gilany (Journal of Infection and Public Health, 2021)
The concept of caseness in the COVID-19 virus is important for early case finding and reporting. These are essential steps for prevention and control. This review defines and differentiates between types of cases and specifies the elements of each case definition in general with their application to COVID-19, where appropriate. These terms and their application are useful for the surveillance team, epidemiologists, clinicians, policy makers as well as the public in general.